Factors affecting the practice of obstetricians on the use of epidural analgesia for labor and delivery - Alvarez, Michelangelo L.
Pain is a normal consequence during labor and delivery among pregnant women. It is also preventable and management schemes like epidural analgesia have been developed to make childbirth a pleasant experience. There are few studies regarding the factors which affect practice of epidural labor analgesia among obstetricians. This is a cross sectional study to determine the factors which may affect the use of epidural analgesia during labor and delivery among obstetricians practicing in 20 tertiary institutions in Metro Manila. A validated questionnaire was administered to measure their level and determine the proportion who practice epidural analgesia during their last five deliveries. Univariate and multivariate analyses using logistic regression were done to determine the association of knowledge, attitude, and the use of epidural labor analgesia. Results reveal that adequate basic knowledge of the obstetrician regarding labor pain and epidural labor analgesia was significantly associated with its on-practice (OR=0.11 95%CI [0.02,0.62]. Favorable attitude of the obstetrician regarding labor pain and epidural labor analgesia was significantly associated wit its practice (OR=2.30 95%CI [1.15,4.61]. Advanced knowledge of the obstetrician regarding labor pain and epidural labor analgesia was not significantly associated with its practice. (OR = 0.93 95%CI [0.42,2.06]). Sensitivity analyses are recommended to increase the understanding of associations between knowledge, attitude and practice of epidural labor analgesia, reduce uncertainty, and to identify errors in the models being studies. Longitudal studies would also be important to better characterize frequency in the practice of epidural labor analgesia, not only for obstetricians based in urban centers like Metro Manila, but also in other areas of the country.